Interseismic Slip Distribution Analysis in East Java - Bagoes Dwi Ramdhani; Irwan Meilano; Endra Gunawan (Indonesian Journal of Geospatial, 2018)
We reexamined GPS stations in Eastern part of java to understand the recent deformation from the convergence zone between the Australian Plate and Sunda Block in East Java. From the seismic record in the subduction zone shown the occurrence of tsunami earthquake in M7.7 in 1994 and several number of earthquakes that potentially become tsunami. To comprehensively obtain the signal in subduction zone, we have to remove the effect of the other major sources deformation in the area of study, as in this study is the block motion from Sunda Block. To remove the block motion of Sunda Block we used the parameters of the model Altamimi (2007) in the GPS field. The used data for this research is several campaign GPS and Continuously GPS data from 2010